Fibrinogen BOE II: Intracerebral hemorrhage associated with a novel compound mutation in a Chinese family with dysfibrinogenemia. Issue 196 (December 2020) - Wang, Xiaoyu; Li, Yang; Luo, Zhongqiu; Hu, Yan; Wang, Rong; Wang, Ping; Ma, Jinjun; Zhang, Jiali; Feng, Xue; Wang, Jianming
Highlights: We found a rare case of congenital dysfibrinogenemia associated with two compound missense mutations c.172G>A (p. Glu58Lys) and c.991A>G (p. Thr331Ala) that we called Fibrinogen BOE II located in FGA which were detected in the patients and his family numbers. The combination of cerebral hemorrhage in the setting of congenital dysfibrinogenemia and a homozygous or compound heterozygous missense mutation was rare. A novel mutation of FGA c.172G>A (p. Glu58Lys) is the first report on a pedigree with congenital dysfibrinogenemia.